Open regionalism in Asia Pacific and Latin America : a survey of the literature - Kuwayama, Mikio (ECLAC SantiagoCL, 1999)
Examines various interpretations and applications of the concept and studies under what circumstances the elements 'open' and 'regionalism' come into contradiction. Reviews briefly the impact of the recent economic crisis on production, trade and investment patterns for each region. Analyzes the appropriate scope and nature of 'new' trade issues to be included in 'deep' integration of developing countries and assesses whether the initiatives through regional agreements can be more effective that those undertaken at the multilateral level. Analyzes the implication of the Uruguay Round commitments on the develoment process and major problems faced in their implementation.